2014
DOI: 10.1056/nejmoa1313984
|View full text |Cite
|
Sign up to set email alerts
|

Obinutuzumab plus Chlorambucil in Patients with CLL and Coexisting Conditions

Abstract: Combining an anti-CD20 antibody with chemotherapy improved outcomes in patients with CLL and coexisting conditions. In this patient population, obinutuzumab was superior to rituximab when each was combined with chlorambucil. (Funded by F. Hoffmann-La Roche; ClinicalTrials.gov number, NCT01010061.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
1,230
9
43

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,350 publications
(1,313 citation statements)
references
References 39 publications
31
1,230
9
43
Order By: Relevance
“…Together with the novel anti-CD20 obinutuzumab [152] and other promising agents (the BCL2 inhibitor ABT-199 [153], the XPO1 inhibitor selinexor [154], CD47 agonist [155]), these treatments may exert different pressure on CLL clonal evolution and may modify prognostic stratification and evolutionary trajectories, as evaluated until now.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the novel anti-CD20 obinutuzumab [152] and other promising agents (the BCL2 inhibitor ABT-199 [153], the XPO1 inhibitor selinexor [154], CD47 agonist [155]), these treatments may exert different pressure on CLL clonal evolution and may modify prognostic stratification and evolutionary trajectories, as evaluated until now.…”
Section: Discussionmentioning
confidence: 99%
“…Results from Phase1b/2 trials indicated that all patients with CLL experienced rapid and sustained removal of B cells in the peripheral blood. 116-119 In Phase 3 trials, GA101 in combination with chlorambucil prolonged overall survival significantly, as well as progression-free survival and increased the complete response rate 120 . In addition, this combination resulted in substantially increased time to next treatment 121 …”
Section: Therapeutic Afucosylated Antibody Drugs Approved For Market mentioning
confidence: 99%
“…Although these Abs showed better activity in vitro and in xenograft models, 3 results from the present clinical trials are unclear as to whether they are better than rituximab, as these novel Abs were used at an optimized pharmacokinetic schedule, but the rituximab schedule was not pharmacokinetically optimized. 4,5 This suggests novel approaches are urgently needed to improve the efficacy of the current anti-CD20 Ab-based therapies.…”
Section: Introductionmentioning
confidence: 99%